Perlindungan Hukum Bagi Pihak Pembeli Atas Batalnya Akta Jual Beli Yang Dibuat Oleh Notaris - srinita, ida ayu gita; Putra, Dewa Nyoman Rai Asmara (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020), 2021)
The benefits of land in human life today are very important, because land can be used as a place to live, for gardening, and can be used for investment, for example leasing or transferring property rights to meet their daily needs. The transfer of property rights is carried out by means of a sale and purchase system, the legal basis is Article 26 of the Basic Agrarian Law, although it does not specifically determine the sale and purchase but describes the transfer or transfer which can be interpreted as a legal event that was deliberately agreed to with the intention of transferring land rights to a debtor who can be said to be a buyer by way of exchange, or by means of a will. The agreement for the transfer of title to land should be put in a written form and must be in accordance with the provisions in which the deed of sale and purchase of land rights must be worked out and legalized by the authorized official, namely PPAT. The certificate made or issued by the PPAT becomes strong evidence in court, because the agreement was made in advance of the PPAT and witnessed by 2 people. The research objective of this journal is to find out how the buyer protects the cancellation of the land sale and purchase deed that was sued by the defendant's stepmother as contained in the Supreme Court Judgment on Reconsideration No. 337 PK / Pdt / 2015. The research in this journal uses empirical research where it starts from a gap between the prevailing norms and the reality of its implementation in society. Then the conclusion of this study which is based on the Supreme Court Reconsideration Decision No. 337 PK / Pdt / 2015, which states that the seller must return the money and interest, to be used by the buyer to buy the land, and vice versa, the buyer must return the land it has bought from the seller. Before selling the land, the seller should have previously negotiated with all members of his family, so that neither party would suffer losses and sue for legal action, because the buyer is in a disadvantaged position